Application of modified magnetic biochar for degradation of organic dyes using advanced oxidation processes - Chin, Catherine Jia Xin (2021)
Untreated wastewater released into the environment has caused water pollution for decades. Recently, researchers found that magnetic biochar could play a big role in combating water pollution especially textile wastewater due to its magnetic separation characteristic. In this study, various types of synthesis methods were analysed from multiple journal papers in the preparation of modified magnetic biochar. This study also established an understanding for the characterisation testings such as Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX), Brunauer-Emmett-Teller (BET) surface area analysis, Fourier Transform Infrared spectroscopy (FTIR) and X-ray Diffraction (XRD) analysis. Besides, the catalytic mechanism of magnetic biochar catalysts in the Fenton process, photo-Fenton process, and photocatalysis process were summarized. The kinetic models were studied and found the most of the processes were followed pseudo-first order reaction. The reusability and stability of magnetic biochar catalysts with their degradation efficiencies in different oxidation processes were also evaluated. The present study proved that various types of biomass can be used as feedstocks in the preparation of magnetic biochar catalyst for degradation efficiency in organic dyes and able to achieve as high as 99.9 %.